2021
DOI: 10.1007/s10755-021-09545-x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Academic Department Chairs: Heightened Complexity, Accentuated Liminality, and Competing Perceptions of Reinvention

Abstract: This article explores the impact of the COVID-19 pandemic on academic department chairs. Through a survey of 172 department chairs in the United States, the central findings of this research—intensified challenges, a multidirectional leadership pivot, and competing perceptions of higher education reinvention—reinforce the liminality of the academic chairperson role, highlight the need for increased training and development opportunities for individuals engaged in this work, and offer a reminder of ensuring tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 22 publications
0
24
0
1
Order By: Relevance
“…However, others characterized the reinvention of higher education in a more skeptical or neutral light, pointing to the existential challenges posed by recent crises and the ongoing uncertainty of what the future might mean for institutions of higher education. As one chair indicated, “There are currently far too many unknowns, recognizing that perspectives on reinvention will continue to evolve as institutions of higher education come to terms with the short‐ and long‐term impact of the pandemic.” These findings from the initial survey reinforce the liminality of the academic chair role, illuminate the challenging conditions within which department leaders work, and offer a reminder of ensuring that the broader perspectives of department chairs are included in efforts to reinvent institutions of higher education (Gigliotti 2021a).…”
Section: Survey Findingsmentioning
confidence: 63%
See 1 more Smart Citation
“…However, others characterized the reinvention of higher education in a more skeptical or neutral light, pointing to the existential challenges posed by recent crises and the ongoing uncertainty of what the future might mean for institutions of higher education. As one chair indicated, “There are currently far too many unknowns, recognizing that perspectives on reinvention will continue to evolve as institutions of higher education come to terms with the short‐ and long‐term impact of the pandemic.” These findings from the initial survey reinforce the liminality of the academic chair role, illuminate the challenging conditions within which department leaders work, and offer a reminder of ensuring that the broader perspectives of department chairs are included in efforts to reinvent institutions of higher education (Gigliotti 2021a).…”
Section: Survey Findingsmentioning
confidence: 63%
“…As summarized further in Gigliotti (2021a), the results of the 2020 survey point to intensified leadership challenges for chairs, the need to pivot extensively in addressing the various stakeholders with whom one engages as department leader, and the existence of competing perceptions of higher education reinvention. For those who expressed a favorable view of reinvention, respondents described the opportunities for innovation, creativity, and growth that have been made possible due to the impact of the pandemic.…”
Section: Survey Findingsmentioning
confidence: 99%
“…This study’s findings are especially important because of the implications for democratizing decision-making in higher education in all countries, not just the US, as well as the ability to describe and compare divergent viewpoints. Although this study focused on institution finances due to the pandemic, Q could be used for other complex issues including social movements on campuses including Black Lives Matter and speech on campus – current issues that require innovative crisis leadership according to Gigliotti ( 2021 ). Within such social, political, and financial issues, the ability to find innovative ideas and viewpoints could lead to innovation in higher education.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the COVID-19 pandemic, Kezar and Holcombe ( 2017 ) declared that today’s higher education leadership challenges necessitate new forms of leadership. Gigliotti ( 2021 ) found that there is a need for administrators to possess crisis leadership competencies especially in within the need for innovation and reinvention within higher education. Similarly, Trakman ( 2008 ) called into question using a twentieth century model for university governance in the twenty-first century.…”
Section: Introductionmentioning
confidence: 99%
“…Latin America and the Caribbean is one of the regions of the world most affected by the global pandemic produced by COVID-19, which has impacted the educational system, transferring it to virtual contexts (Gigliotti, 2021;Popa, 2020;Yang & Huang, 2021). The development of new advanced technologies applied in university teaching (and at all educational levels) rea rms the need to incorporate new dynamics in the classroom (Goodyear, Carvalho, Yeoman, Castañeda & Adell, 2021;Rodríguez, Cantabrana & Cervera, 2021).…”
Section: Introductionmentioning
confidence: 99%